2012
DOI: 10.1002/jnr.23152
|View full text |Cite
|
Sign up to set email alerts
|

Hyperexcitability of inferior colliculus neurons caused by acute noise exposure

Abstract: Noise exposure is one of the most common causes of hearing loss. Recent studies found that noise exposure-induced cochlear damage may change the excitability and tonotopic organization of the central auditory system (CAS). This plasticity was suspected to be related to tinnitus and hyperacusis. However, how cochlear damage affects CAS function and causes these neurologic diseases is still not clear. CAS function is activity dependent, so we hypothesize that a restricted cochlear lesion might disrupt the balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 17 publications
3
19
0
2
Order By: Relevance
“…Neurophysiological studies in animals have shown increased neural activity in the central auditory system following acoustic trauma in various regions including the cochlear nucleus, inferior colliculus, and auditory cortex (e.g. Finlayson and Kaltenbach, 2009; Mulders and Robertson, 2009; Seki and Eggermont, 2003; Niu et al 2013). Recent studies in humans also point to an increase in the gain of central auditory neurons with auditory pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Neurophysiological studies in animals have shown increased neural activity in the central auditory system following acoustic trauma in various regions including the cochlear nucleus, inferior colliculus, and auditory cortex (e.g. Finlayson and Kaltenbach, 2009; Mulders and Robertson, 2009; Seki and Eggermont, 2003; Niu et al 2013). Recent studies in humans also point to an increase in the gain of central auditory neurons with auditory pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Existing theories suggest a potential involvement of both peripheral and/or central mechanisms (Wrinch, 1909;Baguley and Andersson, 2007;Niu et al, 2013). The lack of an animal model of hyperacusis makes it difficult to prove the validity of any postulated mechanisms responsible for this condition.…”
Section: Mechanismsmentioning
confidence: 99%
“…Reduced excitability following noise exposure is also found in the auditory cortex (Insanally, Albanna, & Bao, ; Noreña, Tomita, & Eggermont, ), in the cochlear nucleus (Pilati et al., ), in the IC following juvenile overexposure (Bureš, Grécová, Popelář, & Syka, ), and in a previous study from our lab using the same noise exposure paradigm (Heeringa & van Dijk, ). However, enhanced excitability in the IC following acoustic trauma has also been reported (Niu et al., ; Salvi, Saunders, Gratton, Arehole, & Powers, ). This discrepancy can be explained by several factors, including the type of acoustic trauma (tonal vs. noise, unilateral vs. bilateral, temporary vs. permanent threshold shift), the species and the recovery time, and may need additional research to further elucidate.…”
Section: Discussionmentioning
confidence: 90%
“…This hypothesis considers that steeper RLFs result in greater variation of firing rates when the level of the acoustic stimulus varies, similar to amplitude fluctuations of the sound envelope, and as such increase the synchronization index. In the IC, steeper RLFs are evident immediately after acoustic trauma (Niu, Kumaraguru, Wang, & Sun, ). Furthermore, loss of inhibitory networks can result in steeper RLFs (Caspary, Schatteman, & Hughes, ; Kuenzel, Nerlich, Wagner, Rübsamen, & Milenkovic, ; Pollak & Park, ; Sivaramakrishnan et al., ) and thus can be involved in the observed increased response gains in low‐CF units following acoustic trauma.…”
Section: Discussionmentioning
confidence: 99%